AIRCRAFT TAKE-OFF MASS ESTIMATION IN AVIATION INCIDENT INVESTIGATION PROCESS - Ishchenko, Sergiy (Proceedings of National Aviation University, 2014)
Analysis of existing techniques of aircraft take-off mass estimation in the process of aviation incidentsinvestigation was made. Aircraft take-off mass estimation technique was suggested. It uses parametric information froma flight data recorder that does not need previous parameters filtration, making an obtained estimation more effective.Effectiveness was demonstrated on specific aviation incident example.